Electrophysiological properties of intravenous metoprolol in man. - Rizzon, P (1978)
Electrophysiological changes produced by intravenous (0.1 mg/kg) metoprolol, a new selective beta 1-blocking agent devoid of intrinsic activity, were studied in 16 subjects with estimated normal impulse formation and conduction. The most important effects were sinus bradycardia, mild increase of sinoatrial conduction time, depression of intranodal conduction, and prolongation of AV node refractory periods. Sinus node recovery time and atrial refractory periods were unmodified. Infranodal conduction and the refractory periods of the His-Purkinje system, as well as of the bundle-branches, were unchanged. These effects are compared with those observed after intravenous propranolol, pindolol, and oxprenolol.